On the use of satellite-based vehicle flows data to assess local economic activity: The case of Philippine cities - Eugenia Go; Kentaro Nakajima; Yasuyuki Sawada; Kiyoshi Taniguchi (Asian Development Bank (ADB), 2022)
The lack of suitable data is a key challenge in ex-post policy evaluations. This paper proposes a novel data to measure local economic activities using vehicle counts in each 500 meter (m) x 500 m tile. The metric is derived from high resolution satellite images using a machine learning algorithm. Using the opening of the new international airport terminal in Cebu, Philippines, as a quasi-experiment, we estimate the impact of the new infrastructure on the local economy of Metro Cebu. Results of the difference-in-differences analysis show that the new terminal significantly increased vehicle traffic in urban Cebu. The effect decays with distance from the airport, is stronger in areas where hotels are located, and is most pronounced in the peak months for international tourists. These findings imply that the opening of the new international terminal has enhanced Cebu's local economy through international tourism.
Keywords: R11; 330; transportation infrastructure; satellite imagery data